Proses Berpikir Analitik Dalam Memecahkan Masalah Matematika Berdasarkan Komponen Metakognisi (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2024)
Abstract This research aims to describe 1) the analytical thinking process of students with a high metacognition component in solving mathematical problems and 2) the analytical thinking process of students with a low metacognition component in solving mathematical problems. This research is qualitative. Data was collected using tests, questionnaires, and interview methods. The subjects of this research were two 8th-grade junior high school students selected based on high metacognition and low metacognition components. The research instruments are a pre-questionnaire test, a metacognition component questionnaire, a problem-solving test, and an interview guide. The results of the research show that students' analytical thinking processes have a high metacognitive component in solving mathematical problems, which can be seen from how students use information, link their knowledge to make mathematical models and carry out mathematical calculations, plan strategies and apply problem-solving strategies and carry out evaluations. Meanwhile, the analytical thinking process of students with low metacognition components in solving mathematical problems can be seen from how students use their knowledge to create mathematical models, plan problem-solving strategies, apply them, and conduct evaluations. However, there are errors in the process of planning strategies, implementing strategies, and carrying out evaluations. Keywords: Analytical Thinking Process; Problem-Solving; Metacognition Component. Abstrak penelitian ini bertujuan untuk mendeskripsikan 1) Proses berpikir analitik siswa berkomponen metakognisi tinggi dalam memecahkan masalah matematika, 2) Proses berpikir analitik siswa berkomponen metakognisi rendah dalam memecahkan masalah matematika. Penelitian ini merupakan penelitian kualitatif. Pengumpulan data dilakukan menggunakan metode tes, metode angket, dan metode wawancara. Subjek dari penelitian ini adalah dua siswa kelas 8 SMP yang dipilih berdasarkan komponen metakognisi tinggi dan komponen metakognisi rendah. Instrumen penelitian pada penelitian ini yaitu tes pra angket, angket komponen metakognisi, tes pemecahan masalah, dan pedoman wawancara. Proses berpikir analitik siswa dengan komponen metakognisi tinggi dalam memecahkan masalah matematika terlihat dari bagaimana siswa menggunakan informasi, mengaitkan pengetahuan yang dimiliki untuk dijadikan model matematika dan melakukan perhitungan matematis, merencanakan strategi serta menerapkan strategi pemecahan masalah dan melakukan evaluasi. Sedangkan proses berpikir analitik siswa dengan komponen metakognisi rendah terlihat dari bagaimana siswa dalam menggunakan pengetahuannya untuk membuat model matematis, merencanakan strategi pemecahan masalah dan menerapkannya serta melakukan evaluasi, namun terdapat kesalahan dalam proses merencanakan strategin, menerapkan strategi, dan melakukan evaluasi. Kata Kunci: Proses Berpikir Analitik; Pemecahan Masalah; Komponen Metakognisi.